THE EFFECT OF HPMC AS A GEL BASE AND TWEEN 80 SPAN 80 COMBINATIONS AS EMULGATORS IN ACETOSAL TRANSDERMAL EMULGEL PREPARATIONS - Nirwati Rusli; Muhammad Azdar Setiawan; Nur Hikmawati (Universitas Muhammadiyah Magelang, 2021)
Acetosal or acetyl salicylic acid is a drug that has efficacy as ananalgesic,antipireic, and antiplatelet. Aacetosal undegoes cross-first metabolisism (first passeffect) causing low drug bioavailability. The smal lsolubility of acetosal will affectthe rate of absorption which later affect the intensity of treatment, so transdermaldelivery in emulgel dosage forms can be one of. In this study an experimentalmethod was used by formulating an acetosal transdermal emulgel preparation, asa gel base HPMC was used at a concentration of 4%, 4.5%, 5% also variation oftween 80 concentration 6%, 5%, 4% and variation of Span 80 concentration 4%,5%, 6% as an emulgator. Then a physical evaluation of the preparation wascarried out which included organoleptic tests, pH tests, homogeneity tests,emulsion type tests, viscosity tests, spreadability tests and irritation tests. Theresults of the study showed that the formula 1 emulgel was bone white whileformulas 2 and 3 were white, the pH of the preparation ranged from 4.83-5.57,the preparation was homogeneous with an O/A emulsion type, the viscosity valueof the preparation ranged from 126.67-290 cPa. s, the dispersion value rangedfrom 5.20-6.30 and the preparation was not irritating.